Operando XRD and electrogravimetry coupling to analyze species transfers during redox processes in Ni/Fe-layered double hydroxide. Issue 46 (15th November 2022) - Duquesne, Elise; Betelu, Stéphanie; Seron, Alain; Bricault, Damien; Goldmann, Michel; Ignatiadis, Ioannis; Limagne, Denis; Vlad, Alina; Resta, Andrea; Perrot, Hubert; Sel, Ozlem; Debiemme-Chouvy, Catherine
Abstract : Redox reactions occurring in NiFe-LDH nanoplatelets polarized in LiOH solution lead to anion exchange, cation (electro)sorption and water molecule transfer. Abstract : A new approach was developed by coupling electrochemical quartz crystal microbalance (EQCM) and Grazing Incidence Angle X-ray Diffraction (GIAXRD) to measure operando the current, mass variation and basal spacing of Ni/Fe layered double hydroxide (LDH) under cyclic electrochemical polarization (CEP). It aimed at specifying the redox reactions as well as the ionic and water molecule transfers occurring at the thin LDH film/LiOH aqueous electrolyte interface during the transitional regime and at the stationary state. For a better insight, ac -electrogravimetry was performed to identify the nature, in terms of the molar mass, the kinetics and the concentration variation of the reversibly transferred species associated with the redox reactions. The Ni/Fe-LDH structure is conserved in 1 M LiOH at open circuit potential and during CEPs. In the absence of polarization, CO3 2− anions remain the predominant species in the LDH interlayer spaces. Under polarization, Ni(ii ) oxidation and Ni(iii ) reduction occur within the brucite-like layers of the LDH material as well as the oxygen evolution reaction. During the first 50 CEPs, irreversibly oxidized Ni(iii ) clusters enhance Ni/Fe-LDH conductivity and reversible Ni(iii )/Ni(ii ) redox reaction control anion exchange capacity. OH − anions become the predominant species in the interlayer spaces and are the unique exchanged anionic species during the faradaic process. From the 50th cycle onwards, current, mass variation and basal distance of the electroactivated material oscillate around a stationary value as a function of the applied potential, in agreement with the reversible transfer of Li +, H2 O and OH −, at different kinetics and concentrations.